(untitled) (Global Journal of Science Frontier Research, 2018)
We define and investigate a new class of harmonic functions defined by q -derivative. We give univalence criteria and sufficient coefficient conditions for normalized q -harmonic functions that are convex of order 1. We obtain coefficient inequalities, extreme points distortion bounds, convolution and convex combination condition, and covering theorems for these functions. Further, we obtain the closure property of this class under integral operator.